1987
DOI: 10.1007/bf01810581
|View full text |Cite
|
Sign up to set email alerts
|

Specific polypeptide differences in normal versus malignant human breast tissues by two-dimensional electrophoresis

Abstract: Postmitochondrial and cytosolic polypeptides were extracted from human breast tumors and non-malignant breast tissue and analyzed using high resolution two-dimensional polyacrylamide gel electrophoresis (2D-PAGE). Approximately 800-1000 postmitochondrial and 600-800 silver stained cytosolic polypeptides were detected over the pH range of 4.8 to 7.5 and molecular weight range of 18-120 kDa. The 2D-PAGE patterns of polypeptides from normal and malignant tissue were very similar, although both qualitative and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…In 1984, it was found that most polypeptides were consistently present in both malignant and nonmalignant breast tissues, as only 10 polypeptides differed out of 350 resolved (9). Subsequently, using better technology, it was shown that of ϳ1000 silver-stained cytosolic polypeptides observed, the 2DE patterns from normal and malignant tissue differed in only 6 places qualitatively and only 22 places quantitatively (10,11). A more precise characterization of such polypeptide differences was published in the early 90s with the demonstration of a defect in tropomyosin 1, 2, and 3 expression in mammary carcinoma, suggesting that such abnormalities may play a role in breast neoplasia (12,13).…”
Section: Proteomics Of Breast Tumor Biopsies: True Pitfall?mentioning
confidence: 99%
“…In 1984, it was found that most polypeptides were consistently present in both malignant and nonmalignant breast tissues, as only 10 polypeptides differed out of 350 resolved (9). Subsequently, using better technology, it was shown that of ϳ1000 silver-stained cytosolic polypeptides observed, the 2DE patterns from normal and malignant tissue differed in only 6 places qualitatively and only 22 places quantitatively (10,11). A more precise characterization of such polypeptide differences was published in the early 90s with the demonstration of a defect in tropomyosin 1, 2, and 3 expression in mammary carcinoma, suggesting that such abnormalities may play a role in breast neoplasia (12,13).…”
Section: Proteomics Of Breast Tumor Biopsies: True Pitfall?mentioning
confidence: 99%
“…Early attempts to resolve proteins from breast material by two-dimensional PAGE were hampered by lack of reproducibility, low sensitivity, use of biopsy material containing mixed cell populations, and an inability to obtain sequence information from proteins of interest (15)(16)(17). More recently, significant progress in key areas of proteomics (18,19) has resulted in reports and databases with proteomes for normal and tumorderived breast cell lines in culture (20)(21)(22) and breast tissue from benign and malignant sources (23,24).…”
mentioning
confidence: 99%
“…2D PAGE has been used to search for polypeptide markers for carcinomas of several human tissues, including stomach [22], colon [22,23,24,25], liver [22], kidney [22], prostate [26,27], and brain [28], as well as breast [22,29,30,31]. Steinbeck etal.…”
Section: Discussionmentioning
confidence: 99%